Association of GRIN1, ABCB1, and DRD4 genes and response to antipsychotic drug treatment in schizophrenia. (June 2015) - Pai, Pranita; Arathil, Praveen; Kotambail, Ananthapadmanabha; Nair, Rajesh; Gupta, Meenal; Moily, Nagaraj S.; Kukreti, Ritushree; Jain, Sanjeev; Rai, Padmalatha S.; Gopinath, Puthiya M.; Sharma, Podila S.; Satyamoorthy, Kapaettu
<x xml:space="preserve">Abstract</x> Supplemental Digital Content is available in the text.